Dry heat transfer from the skin surface into textiles: subjective and objective measurement of thermal haptic perception of textiles – preliminary studies. Issue 4 (2nd April 2016) - Ciesielska-Wrobel, Izabela; De Mey, Gilbert; Van Langenhove, Lieva
Abstract : The aim of the study is the assessment of thermal haptic perception of textiles based on subjective and objective evaluations. This subjective evaluation is based on the questioning of human subjects about their thermal perception related to touching textiles. The objective evaluation relies on measurements of temperature changes between fabrics and a human fingertip when textiles are touched. The proposed objective method for estimation of the thermal haptic perception of textiles is far more precise than traditional subjective methods based on the assignment of certain verbal or numerical parameters to the perceived features of textiles. The results provided by the objective methods are congruent with an analytical approach, utilising the heat transfer formula to calculate the heat lost from fingertip skin into textiles, as well as with the theory explaining the boosting of the warm feeling of textiles due to their roughness. It was found that the Q MAX parameter of the textiles is in opposition to the results of subjective assessment and partly to the results of objective assessment.